MORTALITY FROM CARDIOPULMONARY DISEASES 2023–2024 IN BRAZIL, GOIÁS, SANTA ISABEL AND GOIANÉSIA (CIPEEX, 2025)
Cardiorespiratory diseases are pathological conditions that affect the heart and blood vessels, such as acute myocardial infarction (AMI), heart failure, ischemic heart disease, pneumonia, among others. They represent one of the leading causes of mortality in Brazil, especially among the elderly and vulnerable populations. The objective of this study was to analyze mortality data from cardiopulmonary diseases in Goiás, and in municipalities such as Goianésia and Santa Isabel, between the years 2023 and 2024. A bibliographic review methodology was used, presenting a descriptive and quantitative study, based on data obtained from the Mortality Information System (SIM), made available by DATASUS. For this purpose, records with ICD-10 (International Classification of Diseases, 10th revision) codes related to cardiovascular and respiratory diseases, grouped by region and year, were included. From 2022 to 2024, according to the Mortality Information System (SIM), there was an increase in the mortality rate from cardiopulmonary diseases in Brazil, totaling 398,177 deaths, which corresponds to a national average of 11.29 deaths per thousand inhabitants. In the municipality of Goianésia, the number of deaths was significant, with a total of 45 citizens, while in Santa Isabel there was a slight reduction to 6 cases. Therefore, addressing the related risk factors appears crucial to direct more effective public health actions for the population. The findings highlight the persistent relevance of cardiorespiratory diseases as a leading cause of death, requiring continuous investment in public policies focused on prevention, early diagnosis, and effective treatment, especially in regions and municipalities with greater vulnerability and fewer resources.
Keywords: Cardiorespiratory diseases; Mortality; Infarction; Accident prevention